Интегральный оптоэлектронный коммутатор на ДМОП-транзисторах - Politanskyy, L. F.; Lesinskyy, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
A mathematical model of the current–voltage characteristics (I–V curve) of the optoelectronic pair “photodiode–DMOS transistor” has been developed, which makes it possible to establish the relationship between its electrical parameters and the structural and electrophysical parameters of the photodiodes and DMOS transistors. A design of an integrated optoelectronic switch based on DMOS transistors fabricated on “silicon-on-dielectric” structures is proposed. In this configuration, optical control of actuating devices connected to both the source and drain circuits of the key transistor is possible.